2019
DOI: 10.1038/s41598-019-46610-0
|View full text |Cite
|
Sign up to set email alerts
|

A high-quality genome of Eragrostis curvula grass provides insights into Poaceae evolution and supports new strategies to enhance forage quality

Abstract: The Poaceae constitute a taxon of flowering plants (grasses) that cover almost all Earth’s inhabitable range and comprises some of the genera most commonly used for human and animal nutrition. Many of these crops have been sequenced, like rice, Brachypodium, maize and, more recently, wheat. Some important members are still considered orphan crops, lacking a sequenced genome, but having important traits that make them attractive for sequencing. Among these traits is apomixis, clonal reproduction by seeds, prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 79 publications
3
29
0
Order By: Relevance
“…Although an E. curvula genome assembly is available [ 55 ] and we could have used it as a reference genome, for this study we decided to de novo assemble the reads since the sequenced genome belongs to a sexual diploid genotype and the sequences corresponding to the region that determine apomixis might not be present, as was observed by Zappacosta et al [ 54 ] using molecular markers linked to the trait. The assembly quality analysis, performed with Trinity stats, indicated an N50 of 1553 bp, an average contig length of 919.09 bp and a GC content of 46.38%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although an E. curvula genome assembly is available [ 55 ] and we could have used it as a reference genome, for this study we decided to de novo assemble the reads since the sequenced genome belongs to a sexual diploid genotype and the sequences corresponding to the region that determine apomixis might not be present, as was observed by Zappacosta et al [ 54 ] using molecular markers linked to the trait. The assembly quality analysis, performed with Trinity stats, indicated an N50 of 1553 bp, an average contig length of 919.09 bp and a GC content of 46.38%.…”
Section: Resultsmentioning
confidence: 99%
“…Eragrostis curvula (weeping lovegrass), an African grass with cytotypes of different ploidy levels (e.g., 2x–8x) and displaying obligate and facultative apomixis and sexual reproduction [ 46 ], has become a model for the analysis of apomixis mechanisms, due to its particular diplosporous development (meiotic diplospory maintaining the same embryo: endosperm ploidy ratio as in sexual seeds). In recent years, the reproductive mode of this grass was studied extensively, providing information about the cytoembryological aspects of its apomictic–sexual development [ 47 ], differentially expressed (DE) transcripts [ 48 , 49 , 50 , 51 ], epigenetic aspects of apomictic regulation [ 52 , 53 ], mapping of the apomixis locus [ 54 ] and a high quality genome assembly [ 55 ]. Our group also demonstrated that under different internal and external stressful situations, including a change in ploidy, water stress, in vitro culture and intraspecific hybridization, the number of sexual embryo sacs increased in facultative apomictic plants of this grass [ 40 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the lack of information about E. curvula miRNAs and its genome, which is restricted to the sexual diploid Victoria [5], we aimed at identifying the miRNAs based on their possible targets.…”
Section: Resultsmentioning
confidence: 99%
“…The publication of the perl millet genome [Cenchrus americanus (L.) Morrone] (genome size~1.79 Gb; [208]), a minor crop and diploid sexual relative of tetraploid apomictic C. ciliaris L. (Buffelgrass), as well as of the weeping lovegrass genome [Eragrostis curvula (Schrad.) Nees] (genome size~660 Mb; [209]), a diploid sexual forage grass having apomictic polyploid cytotypes, and the genomes of Boechera stricta (genome size 216 Mb) and B. retrofracta (genome size 200 Mb) [210][211][212], two sexual diploid herbs relative to apomictic B. holboellii and B. divaricarpa, represent an effort in that direction. Two recently-initiated projects aiming at sequencing the genome of several sexual and apomictic Boechera species in Canada [213] and Switzerland [214], and the generation of an apomictic Hieracium (predicted genome size 3.6 Gb) genomic and transcriptomic resource [94], may provide the first datasets for sexual-apomictic pair genomic comparisons.…”
Section: Current View and Prospectsmentioning
confidence: 99%